An analysis of timing decision in venture capital staged financing: evidence from India. Issue 12 (29th June 2020) - Panda, Satya Narayan; Gopalaswamy, Arun Kumar
Abstract : Purpose: Staged financing is a prominent feature of the venture capital investment process. With staged financing, venture capitalists (VCs) may choose to either make an investment or delay it at each round. The purpose of this paper is to investigate the influence of market uncertainty, project-specific uncertainty and agency problems on these decisions. Design/methodology/approach: The study uses data from Indian firms that received venture capital funding between 2000 and 2017. The duration between funding rounds is analysed using survival analysis. An accelerated failure time model is used to estimate the influence of market uncertainty, project-specific uncertainty and agency problems on the length of time between funding rounds. Findings: VCs delay investment when there are high levels of uncertainty in the market; if market uncertainty increases by 1%, delay in funding increases by more than 6% (almost a month) on average. There is no statistically significant relationship found between the funding duration and project-specific uncertainty. Agency problems motivate VCs to invest sooner. An increase in agency problems results in a reduction of 55% (almost five months) in the length of time before the next funding round. Practical implications: This study has useful business policy implications. It provides VCs with real option value drivers such as market uncertainty, agency problems, which influence the timing of decisions in staged investment processes. It will help to make the choice between investing and delaying at each round of financing more robust. Further, it is useful for VCs to differentiate between market uncertainty and agency problems against the backdrop of their different implications for staging decisions. Originality/value: Few studies have examined staging decisions from a real options perspective in the context of a developed economy and very few from a developing economy perspective. This study increases understanding of staging decisions in the Indian context.